Italy: a dual labour market in transition: country case study on labour market segmentation - Garibaldi, Pietro; Taddei, Filippo (Geneva, 2013)
"The current paper is one in the series of such country studies. It makes an important contribution to the discussion on contractual segmentation of labour markets, providing an overview of the institutional setup as well as empirical evidence on the extent of segmentation and its implications for various aspects of job quality. The paper also offers a policy perspective on the ways to alleviate the negative consequences of segmentation."